Efeitos do herbicida glifosate sobre o crescimento, enzimas digestivas e parâmetros toxicológicos em piavas (Leporinus sp.) - Salbego, Joseânia (2005)
The effects of glyphosate (1.0 and 5.0 mg/L) on growth, digestive enzymes and toxicology parameters were evaluated in piavas (Leporinus sp.) after 90 days of exposure. A control group was kept in water without herbicide. Fish were fed to satiety twice a day with commercial fish pellets (38% crude protein, Purina®). Water quality was kept by suction of food and fecal residues. The water in the box was renewed every 48 h to maintain herbicide concentration constant during the exposure period. After experimental period (90 days) blood was quickly collected for determining hematological parameters. Liver, white muscle, brain, stomach and intestine were removed and use to determine toxicology parameters and digestive enzymes. After 90 days exposure, fish weight gain, specific growth rate, and feed efficiency wede reduced as glyphosate concentration increased in the water. The activity of all digestive enzymes verified increased with the increase of glyphosate concentration. Results indicate that AChE activity significantly decreased in the brain of fish exposed to 5 mg/L of glyphosate, but in the muscle this parameter was increased in the fish exposed to 1mg/L of glyphosate. Exposure to this herbicide produced a decrease in all hematological parameters tested in both concentrations used. Fish exposed to all glyphosate concentrations showed a significant decrease in liver glycogen and glucose, but a significant increase in muscle glycogen after exposure to 5 mg/L herbicide. Muscle glucose was not altered. Lactate and protein (5 mg/L) of fish exposed to all glyphosate concentrations increased in the liver. Similar results were showed in the muscle for lactate, but protein was reduced after exposure to 5 mg/L of glyphosate. These results indicate that glyphosate affect growth, hematologic and metabolic parameters as well digestive enzymes of piavas. All parameters tested may be indicators of herbicide contamination after prolonged exposure.